Using Oncotype DX as an additional treatment decision tool in early breast cancer: a retrospective analysis from a single institution in Taiwan - Chang, Chuan-Hsun; Lin, Yi-Hsien (Therapeutic Radiology and Oncology; Vol 2 (February 2018): Therapeutic Radiology and Oncology, 2018)
Background: Gene expression analysis is increasingly employed in breast cancer. This study is aimed to investigate the application of Oncotype DX as an additional treatment decision tool in early breast cancer in our institute. Methods: Early breast cancer patients using Oncotype DX as a treatment decision tool at Cheng Hsin General Hospital from 2009 to 2014 were analyzed retrospectively. Thirty patients were enrolled. Results: Seventeen patients (56.7%) had a low recurrence score (RS); 9 (30%) had intermediate RS; and 4 (13.3%) had high RS. All those with high RS received adjuvant chemotherapy, and none of the low and intermediate RS groups had adjuvant chemotherapy. The concordance of ER, PR, HER2/neu immunohistochemistry (IHC), and HER2/neu fluorescence in situ hybridization (FISH) was 96.7%, 90.0%, 100%, and 93.3%, respectively. No local recurrence and distant metastasis were reported. Conclusions: This study offers our experience of using Oncotype DX in Taiwan. The results show a significant impact on the patient’s decision of choosing adjuvant chemotherapy for early breast cancer patients. To confirm these findings, large scale studies are warranted.